Potential role of microbial pathogens in control of red palm weevil (Rhynchophorus ferrugineus) ‐ A Review. Issue 4 (29th June 2017) - Yasin, Muhammad; Wakil, Waqas; El‐Shafie, Hamadttu A.F.; Bedford, Geoffrey O.; Miller, Thomas A.
Abstract: The invasive Red Palm Weevil (RPW), Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae), is one of the most destructive pests of ornamental and economically important palms globally. It has been found in 50 % of date‐growing and 15 % of coconut‐producing countries in the world. Synthetic organic insecticides have been the default method to combat this pest, but they are clearly inefficient due to the secretive nature of the insect and there is concern about non‐target effects from blanket spraying. For this reason, there is increasing interest in biological control methods such as the possible use of microbial entomopathogens, which might be incorporated into IPM approaches. In this review we summarize research work on microbial control agents, their effectiveness against RPW and their integration with other control measures.